THE PROBLEM OF ECOLOGY IN THE CONTEXT OF MODERN SOCIETY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This thesis analyzes the problems of ecology in the context of modern society. Environmental problems mainly include issues such as industrial pollution, climate change, and the reduction of biological diversity, which occur as a result of human activity. The thesis shows the importance of measures necessary to solve environmental problems, including environmental education, introduction of innovative technologies and international cooperation. Since ecological problems pose a serious threat to the future of humanity, it is emphasized that every person, society and state have a great responsibility.